Benefits and dynamics of learning gained through volunteering: A qualitative exploration guided by seniors' self-defined successful aging. Issue 3 (3rd March 2016) - Chen, Li-Kuang
ABSTRACT: Social participation is an important strategy in promoting successful aging. Although participating in volunteering has been proven to benefit older adults' health and well-being, we often ignore its role as a process of learning while helping others. The purpose of this study was to use the self-defined successful aging concept of seniors to explore the roles of learning through volunteering in Taiwan, an Asian country with a dramatically fast growth of its older population. Using in-depth interviews of 31 older adults who fit the participation criteria, this study concluded that learning through volunteering, a form of informal learning, is a holistic approach to successful aging, including physical, psychological, social, and spiritual dimensions. Through the learning, volunteering benefited the volunteers' self-defined successful aging by (a) establishing a substantial and expanding life, (b) building and improving relationships, (c) enhancing positive changes and self-evaluation, (d) promoting physical and psychological health, and (e) triggering treasures and preparations for the rest of life. The five dimensions can work alone but often interactively facilitate the seniors' successful aging. These findings enrich the existing body of knowledge by revealing the dynamic between learning through volunteering and self-defined successful aging in Taiwan. Policy makers and practitioners might use these findings to popularize elder volunteerism and other forms of elder learning activities that will then better equip older adults to fulfill their desire for a successful old age.